2013
DOI: 10.1021/ic3026842
|View full text |Cite
|
Sign up to set email alerts
|

BTBPs versus BTPhens: Some Reasons for Their Differences in Properties Concerning the Partitioning of Minor Actinides and the Advantages of BTPhens

Abstract: Two members of the tetradentate N-donor ligand families 6,6'-bis(1,2,4-triazin-3-yl)-2,2'-bipyridine (BTBP) and 2,9-bis(1,2,4-triazin-3-yl)-1,10-phenanthroline (BTPhen) currently being developed for separating actinides from lanthanides have been studied. It has been confirmed that CyMe4-BTPhen 2 has faster complexation kinetics than CyMe4-BTBP 1. The values for the HOMO-LUMO gap of 2 are comparable with those of CyMe4-BTBP 1 for which the HOMO-LUMO gap was previously calculated to be 2.13 eV. The displacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
133
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(149 citation statements)
references
References 90 publications
15
133
1
Order By: Relevance
“…In previous studies numerous different conditions have been applied, most often using a mixture of alcohol (methanol, ethanol or 2-propanol) and water as a solvent. [12][13][14][15][16][17][18][19][20][21][22][23] A comparison of these studies has shown that the water content as well as the alkyl chain of the alcohol have a considerable impact on the stability constants of the formed complexes. 13 Therefore, a detailed knowledge on the influence of the solvent is essential for the comparison of different ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies numerous different conditions have been applied, most often using a mixture of alcohol (methanol, ethanol or 2-propanol) and water as a solvent. [12][13][14][15][16][17][18][19][20][21][22][23] A comparison of these studies has shown that the water content as well as the alkyl chain of the alcohol have a considerable impact on the stability constants of the formed complexes. 13 Therefore, a detailed knowledge on the influence of the solvent is essential for the comparison of different ligands.…”
Section: Introductionmentioning
confidence: 99%
“…This may in part be due to the requirement for a conformational change in SO 3 -Ph-BTBP from its preferred trans-conformation to the less favoured cis-conformation prior to metal binding [9,11,12], Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…Such a requirement for a conformational change has been proposed, at least in part, to be responsible for slow kinetics of extraction of both An(III) and Ln(III) species by hydrophobic CyMe 4 based versions of BTBP compared to CyMe 4 based equivalents of BTP and BTPhen [9,11,12]. Thus, we would expect such extraction kinetics to also be slow for Fe 3+ extraction, resulting in the lack of an observed increase in the rate of reductive or transpassive dissolution for both SS304L and SS316L (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A striking breakthrough came from the development of another more preorganized tetradentate -heterocyclic ligand, 2,9-bis(1,2,4-triazin-3-yl)-1,10-phenanthroline (BTPhen), by the scientists of Reading University [26][27][28]. BTPhen has been regarded as one of the most promising ligands for the MA(III) separation from highly acidic waste until now.…”
Section: Introductionmentioning
confidence: 99%